Raymond Williams and “structures of feeling”: the affects as social creativity - Ribeiro, Adelia Maria Miglievich (2020)
I return to the relevance of the first generation of British Cultural Studies by examining Raymond Williams's specific contribution to dialogue in the contemporary "affective turn" in the social sciences. To this end, I explore his concept of a “structure of feelings” that goes back to the possibility of the scholar to see the ways in which a given person and group articulate their experiences in response to a previous situation. The movement of articulation itself configures culture for Williams's “new materialism”, attentive to forms of emergence and thus to social transformation. I revisit the notions of Stimmung and mood to get closer to the description of "common affects" that intertwine bodies and materials and are able to infect a time. In the end, I want to demonstrate the actuality of the Welsh critic who moved into the British “new left” also working on the renewal of Marxism, replacing Louis Althusser's “structure” with an intricate web of complex relationships that turn into real dynamics of life in which affecting each other is an “unexpected potential for meaning” (GUMBRECHT, 2014). I leave readers with a chance to judge such powers as advancements or setbacks in a desirable social order, only to ensure that change begins in the most subtle aspects of social life.